2018
DOI: 10.1111/zph.12533
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐resistant Shiga toxin‐producing Escherichia coli: An overview of prevalence and intervention strategies

Abstract: Shiga toxin‐producing Escherichia coli (STEC) are foodborne pathogens that can cause severe diseases, including bloody diarrhoea and kidney failure, in humans, while remaining harmless to its primary reservoir hosts, cattle. Antibiotics such as azithromycin, fosfomycin and meropenem are being used and recommended in the treatment of early‐stage STEC (mainly E. coli O157:H7) infections, as these are reportedly effective in preventing Shiga toxin release and kidney failure while eliminating the pathogen. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 139 publications
5
53
1
Order By: Relevance
“…E. coli O157: H7 AC188 was less susceptible to STP than ATCC 43888; this is correlated with previous reports that have shown the development of resistance of clinical isolates to aminoglycosides because of indiscriminate use of antimicrobials [10,26]. Unlike that observed with STP, the Ib-M peptides showed similar MICs in both strains of E. coli O157: H7.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…E. coli O157: H7 AC188 was less susceptible to STP than ATCC 43888; this is correlated with previous reports that have shown the development of resistance of clinical isolates to aminoglycosides because of indiscriminate use of antimicrobials [10,26]. Unlike that observed with STP, the Ib-M peptides showed similar MICs in both strains of E. coli O157: H7.…”
Section: Discussionsupporting
confidence: 88%
“…To extend the previous findings on the antimicrobial activity of the Ib-M peptides, this work evaluated its antibacterial properties against E. coli O157: H7, the most prevalent serotype of shigatoxigenic E. coli (STEC), a well-established bacterial foodborne pathogen, whose overall incidence is estimated in approximately 2.8 million cases of acute gastrointestinal disease annually [8]. The STEC-induced illness is characterized by bloody diarrhea, hemorrhagic colitis, and complications associated with the development of hemolytic uremic syndrome [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that individuals with a low bacterial richness are characterized by a more inflammatory phenotype [56]. The association between increased Enterobacter and decreased renal function has been confirmed in many studies [57,58]. The mechanisms behind these phenomena may be attributable to the inflammatory immune response and intestinal susceptibility of IgAN.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, although antibiotics are not used to clear STEC in cattle, the presence of AR genes in STEC could contribute towards increased dissemination of antibiotic resistance in the environment. Several studies in the US and abroad have reported resistance to aminoglycosides, β-lactams, carbapenems, cephalosporins, erythromycin, phenicols, streptomycin, sulpha-drugs, and tetracyclines, besides multidrug resistance in STEC isolated from humans and animals [31,76,[79][80][81][82]. Meta-analysis of the AR data for the six control O157, as annotated in the Pathosystems Resource Integration Center (PATRIC) Bioinformatics Resource Center (https://www.…”
Section: Discussionmentioning
confidence: 99%